Effects Of Teaching Using Interactive Whiteboard On Mathematics Achievement And Attitude Towards Mathematics Word Problem Of Grade Two Female Pupils In Kuwait - Alazemi, Afrah Raan (2021)
It is irrefutable that many pupils in different stages struggle with mathematics especially MWP in the elementary stage and this appears in their low performance in their exams. In Kuwait, there is a low level of students’ achievement in mathematics programs, just as it is common in some Arab countries because of lack of interactive technology in teaching MWP and teachers’ lack of focus on pedagogical engagement. The purpose of this study is to examine the effects of teaching using interactive whiteboard on the mathematics achievement and attitude towards mathematics word problem of grade two female pupils in Kuwait. The study adopts the quantitative approach through a quasi-experimental research design to achieve the research objectives. The study samples 48 female pupils in Grade two with 24 pupils in the classroom with interactive whiteboard (experimental group) and 24 pupils in the classroom with conventional whiteboard (control group). The sample of this study was selected using the purposive sampling technique. Two instruments, namely achievement test in mathematics word problem and attitude towards mathematics word problem questionnaire were used to collect data. The data collected were analysed using independent samples t-test. The results reveal that there were no significant differences in achievement in (pretest) and attitude towards (pre-survey) mathematics word problem between grade two pupils who learned through teaching using an interactive whiteboard and grade two pupils who learned through teaching using a conventional whiteboard. The results show that there were significant differences in achievement in (post-test) and attitude towards (post-survey) mathematics word problem between grade two pupils who learned through teaching using an interactive whiteboard and grade two pupils who learned through teaching using a conventional whiteboard. The results also depict that there were significant differences in the retention of achievement in (retention test) and the retention of attitude towards (retention survey) mathematics word problem between grade two pupils who learned through teaching using an interactive whiteboard and grade two pupils who learned through teaching using a conventional whiteboard. Theoretically, this study has theoretical implication for the theory of constructivism as it helps to strengthen the mode of learning and teaching via technologies. It helps to strike a balance between pedagogical skills, collaborative learnings and understanding of mathematics word problem. This study contributes to the on-going debates about learning technologies and in the field of education policy making. Finally, this study concludes that IWBs have significant effects on pupils in improving their achievement in MWP and attitudes towards MWP.